A Review of Islamic Law on Property Ownership Rights from the Perspective of Fiqh Muamalah - Saipul Bakhri; M. Wahid Rangkuti; Ayani Yusriza Mahendra; M. Arif Arifin; Nursania Dasopang (Al Urwah : Sharia Economics Journal, 2025)
This study examines Islamic law on property ownership rights from the perspective of Islamic jurisprudence (fiqh muamalah) amidst economic inequality and the lack of a national Sharia-based property codification. The aim is to analyze the classification, causes, types, and management of assets for practical guidance. Using a qualitative normative approach through literature review, the population includes Islamic jurisprudence (fiqh muamalah) literature, with a purposive sample of 20-30 primary (Quran, hadith) and secondary (fiqh texts, journals 2021-2025) sources. Instruments in the form of Sharia documents were analyzed descriptively and analytically with triangulation and synthesis of the maqasid (maqasid) of Sharia. The results show that assets (al-mal) are a divine trust, etymologically human instincts and terminologically valuable assets to be owned and transacted, classified as private, public, state, protected by the daruriyyat (private), hajiyyat (private), and tahsiniyyat (private). Ownership arises from ihya' mawat (promise), legal contracts, inheritance, and business proceeds, with an emphasis on halal distribution such as zakat. In conclusion, sharia-based codification is needed to prevent exploitation and realize just prosperity.